Building Diaspora : Filipino Cultural Community Formation on the Internet - Ignacio, Emily, 1970- (Book collections on Project MUSE., 2004)
Building Diaspora heralds an important development in cultural studies, ethnic studies, the sociology of media, and globalization. Emily Ignacio brings an extended, incisive empirical investigation that is still quite rare in the theory-heavy yet data-light field of cyberspace cultural studies. She carefully crafts a framework in which to showcase the itinerant ideas and desires of Filipinos talking to each other from various geographical locations.""--Martin Manalansan IV, University of Illinois, Urbana-Champaign The dramatic growth of the Internet in recent years has provided o.